Analisis Pengendalian Biaya Produksi Pada Perusahaan Manufaktur Melalui Penerapan Akuntansi Pertanggungjawaban - I Made Deva Samadhinata; I Gusti Ayu Purnamawati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
This study aims to analyze the control of production costs with the application of accountability accounting conducted by the company CV.Cok Konfeksi in Bali. This research method in descriptive qualitative which consists of two types of data, namely primary and secondary data. Data collection used is interviews, observation and documentation. The informants interviewed in this study were manager, treasurer cok konfeksi 1 and treasurer cok konfeksi 2 with a total of informants were 3 people. The results of research that researchers heve done is know that CV.Cok Konfeksi implements responsibility accounting properly by reporting, monitoring, and evaluating its perfomence and financial system, one of which is production costs.